Sayyid Qutb : an intellectual biography - Šabasevičiūtė, Giedrė (Modern intellectual and political history of the Middle East., 2021)
"Standing at the crossroads of biography and intellectual history, this book seeks to trace the debates on literature between writers, Muslim scholars, and Islamists in Egypt between 1900 and 1960. To understand these debates, it follows the intellectual career of Egyptian writer and late-life Islamist, Sayyid Qutb"--